Gestão para o processo de desenvolvimento de software científico utilizando uma abordagem ágil e adaptativa na microempresa - Berni, Jean Carlo Albiero (2010)
The scientific software development has particularities that, frequently, differ from usual rules in commercial software production. The emerging requirements that appear while the development process is running, needs for often communication between stakeholders (researchers) and developers, and necessary ways to customize the process, make this kind of software building activity more iterative than conventional. Agile methodologies for software development arise as alternatives for prescriptive methods and, as analyzed in this research, have the answer for how to build software in dynamics environments. In this work is proposed a management method for the scientific software development process. The agile methodologies Scrum and Extreme Programming were tailored to reach the peculiarity of scientific process, and the method definition. The model was applied in real projects in a small business company for validation and, through a qualitative analysis, the improvement of the development process could be checked.